2020
DOI: 10.1016/j.yjmcc.2019.11.123
|View full text |Cite
|
Sign up to set email alerts
|

A collagen hydrogel loaded with HDAC7-derived peptide promotes the regeneration of infarcted myocardium with functional improvement in a rodent model

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…[119][120][121] These studies also showed an increase in endogenous BMCs homing to the heart after injection of HA hydrogels modified with recombinantly expressed SDF-1 119,120 or with collagen I hydrogels embedded with histone deacetylase 7 peptide. 121 In both cases, enhanced angiogenesis and recovery of left ventricular function were observed, and infarct size decreased up to fourfold in comparison with the control models. Recent clinical trials have reported that injecting patients suffering from heart failure with acellular alginate hydrogels is safe and increased the rate of recovery when combined with standard treatments.…”
Section: Hydrogels As Transplant Matricesmentioning
confidence: 74%
See 2 more Smart Citations
“…[119][120][121] These studies also showed an increase in endogenous BMCs homing to the heart after injection of HA hydrogels modified with recombinantly expressed SDF-1 119,120 or with collagen I hydrogels embedded with histone deacetylase 7 peptide. 121 In both cases, enhanced angiogenesis and recovery of left ventricular function were observed, and infarct size decreased up to fourfold in comparison with the control models. Recent clinical trials have reported that injecting patients suffering from heart failure with acellular alginate hydrogels is safe and increased the rate of recovery when combined with standard treatments.…”
Section: Hydrogels As Transplant Matricesmentioning
confidence: 74%
“…Several key examples have shown that acellular injectable hydrogels of different compositions are safe for cardiac implantation in murine models 119‐121 . These studies also showed an increase in endogenous BMCs homing to the heart after injection of HA hydrogels modified with recombinantly expressed SDF‐1 119,120 or with collagen I hydrogels embedded with histone deacetylase 7 peptide 121 . In both cases, enhanced angiogenesis and recovery of left ventricular function were observed, and infarct size decreased up to fourfold in comparison with the control models.…”
Section: Soft Biomaterials For Sc Deliverymentioning
confidence: 89%
See 1 more Smart Citation
“…The current research focuses on addressing these limitations to employ dECM as a clinically relevant biomaterial for myocardial regeneration. Better cardiac output and ejection fraction when compared to control groups (Ifkovits et al, 2010) α (cyclodextrin) CD-MPEG-PCL-MPEG hydrogel -Rabbits Prevented scar expansion and wall thinning; Increased ejection fraction when compared to the control groups (Jiang et al, 2009) Collagen I loaded 7-amino-acid-peptide hydrogel H9C2 cardiac myoblast C57/B6 mice Increased stem cell recruitment and infarct wall thickness; Improved angiogenesis (Zhang et al, 2019b) gelatin methacrylate (GelMA)-(Au/SiO2) NPs H9C2 rat cardiomyoblasts -Improved cell adhesion and proliferation in the GelMA-Au/SiO2 hydrogel compared to control; Uniform cell alignment in the GelMA-Au/SiO2 hydrogel (Maharjan et al, 2019) Dextran-poly (e-caprolactone)-2-hydroxylethyl methacrylate/poly (N-isopropylacrylamide) [Dex-PCL-HEMA/PNIPAM] -MI rabbits Decreased scar expansion and thinning of wall compared with controls; Attenuated left ventricular systolic and diastolic dilatation; Increased left ventricular ejection fraction (Wang et al, 2009) Gelatin/Laponite® hydrogel loaded with secretome (nSi Gel+) Human umbilical vein endothelial cells (HUVECs)…”
Section: Decellularized Tissuesmentioning
confidence: 99%
“…Collagen as the main component of the native ECM has been widely used as an appropriate biomaterial for cell encapsulation due to its favorable biocompatibility, degradation, and tissue regeneration potential properties [4,17]. Encapsulation of MSCs within injectable collagen has demonstrated not only preservation of cells' differentiation potential, but also cell viability upon in vivo implantation [18].…”
Section: Introductionmentioning
confidence: 99%